Usefulness of home blood pressure monitoring in masked resistant hypertension - Barochiner, Jessica (Revista del Hospital Italiano de Buenos Aires, 2022)
Resistant hypertension is associated with increased cardiovascular risk. In our study, we found that masked resistant hypertension is frequent and easily detectable through home blood pressure monitoring, and it is also an independent predictor of cardiovascular events.
Keywords: cardiovascular events; home blood; pressure monitoring; masked uncontrolled hypertension; mortality; resistant hypertension